Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s00247-007-0511-4
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging findings of eosinophilic cystitis in an 8-year-old girl

Abstract: Eosinophilic cystitis is a rare inflammatory condition of the urinary bladder of unknown aetiology and characterized by eosinophilic infiltration of the bladder wall. We report the unique MR findings of eosinophilic cystitis in an 8-year-old girl who presented with peripheral eosinophilia. MR imaging revealed smooth and nearly circumferential thickening of the bladder wall showing distinct low signal intensity on T2-weighted images, which may histologically represent high cellularity due to massive eosinophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Tamai et al report a case of eosinophilic cystitis in an 8-year-old girl where MRI showed distinct low signal intensity on T2-weighted images, which was suggested to represent high cellularity due to massive eosinophilic infiltration [ 14 ]. Eosinophilic cystitis has been reported isointense on T2-weighted sequences in the adult population [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tamai et al report a case of eosinophilic cystitis in an 8-year-old girl where MRI showed distinct low signal intensity on T2-weighted images, which was suggested to represent high cellularity due to massive eosinophilic infiltration [ 14 ]. Eosinophilic cystitis has been reported isointense on T2-weighted sequences in the adult population [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found 4 patients who had HES and EC including the present patient and 14 EC patients who had no etiology and an eosinophil count as described in the report [3,4,5,6,7,8,9,10,11,12,13,14,15]. Of the 14 patients reported as EC, 5 had an eosinophil count of ≥1,500/μl on at least one occasion without apparent cause of eosinophilia, which suggests that these patients had HES (table 1).…”
Section: Resultsmentioning
confidence: 62%
“…The EC sometimes (43% of the cases) [9] correlates with parasitosis, asthma, and allergy, revealing a possible relationship between EC and a disorder of the immune system. In contrast, NA is thought to result from urothelial metaplasia in response to urothelial injury [10], although some authors suggest it derives from exfoliated distal renal tubule cells [11].…”
Section: Discussionmentioning
confidence: 99%